2016
DOI: 10.1111/1365-2664.12832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variation in the abundance and distribution of prey on the foraging success of central place foragers

Abstract: 1. Seabirds and pinnipeds are vulnerable to reductions in prey availability, especially during the breeding season when spatial constraints limit their adaptive capacity. There are growing concerns about the effects of fisheries on prey availability in regions where large commercial fisheries target forage fish.2. For breeding seabirds and pinnipeds, prey availability depends on a combination of abundance, accessibility, patchiness, and distance from the colony. An understanding of the aspects of prey availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…Non‐random foraging site selection and foraging area fidelity are well documented for seabirds (e.g. Cairns & Schneider, ; Gorke & Brandl, ), including penguins (Baylis et al, ), and the foraging locations of diving seabird species are known to be correlated with favourable depth distributions of their prey (Boyd et al, , ; Zamon et al, ). Foraging site selection by African penguins in Algoa Bay, especially for penguins breeding on Bird Island, may be related to the dynamic nature of oceanographic processes in this region (van Eeden, Reid, Ryan, & Pichegru, ; Goschen, Schumann, Bernard, Bailey, & Deyzel, ) and the influence that these processes have on the three‐dimensional distribution of small pelagic fish around Bird and St Croix islands (McInnes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Non‐random foraging site selection and foraging area fidelity are well documented for seabirds (e.g. Cairns & Schneider, ; Gorke & Brandl, ), including penguins (Baylis et al, ), and the foraging locations of diving seabird species are known to be correlated with favourable depth distributions of their prey (Boyd et al, , ; Zamon et al, ). Foraging site selection by African penguins in Algoa Bay, especially for penguins breeding on Bird Island, may be related to the dynamic nature of oceanographic processes in this region (van Eeden, Reid, Ryan, & Pichegru, ; Goschen, Schumann, Bernard, Bailey, & Deyzel, ) and the influence that these processes have on the three‐dimensional distribution of small pelagic fish around Bird and St Croix islands (McInnes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The depth distribution of prey plays an important role in how predators use their habitat (Benoit‐Bird et al., ; Boyd et al., ; Carroll et al., ). By exploring the relationship between the number of PCE with dive depth and duration, we have shown that two species, guillemots and razorbills, clearly made different decisions while exploiting the water column.…”
Section: Discussionmentioning
confidence: 99%
“…In other diving marine predators (e.g., the little penguin (Eudyptula minor), Peruvian booby (Sula variegata), and Guanay cormorant (Phalacrocorax bougainvilliorum)), the distribution of prey capture events and dives in the water column match the local distribution of their prey (Boyd et al, 2016;Carroll et al, 2017). Therefore, we assumed that the number of PCE performed in each dive is a measure of foraging effort occurring in the presence of prey.…”
Section: Individual Dive Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations of aerial seabirds and diving species, whether birds, fish or mammals, are conspicuous worldwide and likely to include important positive interspecific associations (Evans, 1982;Au and Pitman, 1986;Camphuysen and Webb, 1999;Clua and Grosvalet, 2001;Davoren et al, 2010;Goyert et al, 2014;Boyd et al, 2016). The example of diving predators pushing bait balls of fodder fish to the surface is the most familiar of interspecific associations of seabirds in the open ocean (Cafaro et al, 2016).…”
Section: Positive Interactions Among Marine Predatorsmentioning
confidence: 99%